Three‐dimensional assessment of umbilical vein deviation angle for prediction of liver herniation in left‐sided congenital diaphragmatic hernia. (27th December 2017) - Volpe, N.; Mazzone, E.; Muto, B.; Suprani, A.; Fanelli, T.; Kaihura, C. T.; Dall'Asta, A.; Pedrazzi, G.; Del Rossi, C.; Silini, E. M.; Magnani, C.; Volpe, P.; et al.
ABSTRACT: Objectives: To introduce a new sonographic marker of intrathoracic liver herniation in fetuses with left‐sided congenital diaphragmatic hernia (CDH). Methods: In a consecutive series of fetuses with isolated CDH, an ultrasound volume of the fetal abdomen was acquired. On this volume, offline calculation of the angle formed by the midline of the abdomen (joining the center of the vertebral body to the abdominal insertion of the umbilical cord) and a second line joining the center of the vertebral body to the intra‐abdominal convexity of the umbilical vein was carried out to give the umbilical vein deviation angle (UVDA). The UVDA was measured in a group of normal fetuses selected as controls. At follow‐up, the presence of liver herniation was investigated in all cases of CDH. UVDA values were compared between the CDH group and controls, and between CDH 'liver‐up' vs 'liver‐down' cases. A receiver–operating characteristics (ROC) curve was constructed to identify a cut‐off value of the UVDA with the highest accuracy in predicting liver herniation in the CDH group. Results: Between 2009 and 2015, 22 cases of left‐sided CDH were included in the study group, of which nine cases had liver herniation. Eighty‐eight normal fetuses were recruited as controls. The UVDA was significantly higher in the cases vs controls (15.25 ± 7.91° vs 7.68 ± 1.55°; P < 0.0001). Moreover, the UVDA was significantly increased in CDH fetuses with liver‐up vs liver‐down (21.77 ± 8.79° vs 10.75 ± 2.10°; P < 0.0001). On ROC curve analysis the UVDA showed good prediction of liver herniation (area under the ROC curve, 0.94; P < 0.0001) with the best cut‐off of 15.2°, yielding a sensitivity of 89% and a specificity of 100% ( P < 0.0001). Conclusions: In fetuses with CDH, umbilical vein bowing may be quantified by measuring the UVDA using three‐dimensional ultrasound. This sonographic marker seems to be an accurate predictor of liver herniation in left‐sided CDH. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.